2007
DOI: 10.12693/aphyspola.112.1318
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties of Fe3O4Films on Fe(001)

Abstract: We investigated the magnetic properties of ultrathin magnetite films deposited directly on MgO(001) and on a Fe(001) buffer layer. In both cases the magnetite surface structure could be identified using low energy electron diffraction. The conversion electron Mössbauer spectroscopy measurements proved that, for magnetite films deposited on the Fe buffer, superparamagnetic relaxation was strongly suppressed. The effect of a Fe overlayer on the magnetite film grown directly on MgO is considerably weaker. Longitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
3
1
Order By: Relevance
“…1͑a͒, is an asymmetric line that can be decomposed into a broadened single line and a doublet labeled with M and I, respectively. 24 The CEMS spectrum demonstrates the lack of a long-range magnetic order, contrary to observations by Martinez Boubeta et al, 26 who found a ferromagnetic order for films as thin as 4 ML. 1͑a͒ shows an isomer shift representative for metallic iron, which constitutes 69% of the film.…”
Section: Resultscontrasting
confidence: 68%
See 1 more Smart Citation
“…1͑a͒, is an asymmetric line that can be decomposed into a broadened single line and a doublet labeled with M and I, respectively. 24 The CEMS spectrum demonstrates the lack of a long-range magnetic order, contrary to observations by Martinez Boubeta et al, 26 who found a ferromagnetic order for films as thin as 4 ML. 1͑a͒ shows an isomer shift representative for metallic iron, which constitutes 69% of the film.…”
Section: Resultscontrasting
confidence: 68%
“…Therefore, separated islands cannot be observed using this method. 24,25 It has to be emphasized that for the survey presented here a polished substrate was used. So far, AFM investigations for film thicknesses down to 1 nm are reported, 18 albeit differences in sample preparation have to be taken into account, as these play a crucial role for the resulting structures.…”
Section: Introductionmentioning
confidence: 99%
“…The films were prepared applying the growth procedure and the LEED and CEMS characterization in a multi-chamber UHV system reported previously [4,5] Table) and the bi-layer films (S4, S6, S7) were annealed for 30 min, respectively, at 520 K and 800 K. For underlying the annealing effect, we study two bi-layer films with similar thickness, one under post-annealing (S6) and another one (S9) without annealing (non-ann.). Besides, in order to get clear features of the Fe layer beneath the Fe 3 O 4 layer, we also study a bi-layer film with a thin Fe 3 O 4 layer (≈ 8 nm) deposited on a thick Fe buffer (≈ 50 nm, S8 non-ann.)).…”
Section: Methodsmentioning
confidence: 99%
“…bi-layer magnetite film or Fe 3 O 4 /Fe/MgO(001) film). The film characterizations by low energy electron diffraction (LEED) and conversion electron Mössbauer spectroscopy (CEMS) have revealed a surface oxidation and Mg outdiffusion from MgO substrate into the film for the single-layer Fe 3 O 4 films, whereas no Mg diffusion was observed for the bi-layer ones, since it could be prevented by the Fe layer [4,5].…”
Section: Introductionmentioning
confidence: 99%